TECHNO-ECONOMIC STUDY OF ALUMINIUM ALLOY AND STEEL AS MATERIALS FOR DECKHOUSES OF OFFSHORE SUPPORT VESSELS - M, Ferry (The Indonesian Journal of Naval Architecture, 2013)
Aluminium alloy is a relatively more expensive material than steel although its weight is one-third of the steel. Thus the use of steel as a structure adds additional weight by 60%; and when used as deckhouses would raise the GM and scarifying the stability of the offshore support vessel. This paper reviews the merit and demerit of Aluminium alloy and steel focusing on fabrication and assembly, and maintainability cost typical of a 60.0m offshore support vessel operating between Kemaman port and offshore oil rigs in the South China Sea. Mathematical equation was used to calculate the weight of the materials used to construct the deckhouses. Also, net present value and payback period calculations were performed to indicate the economic benefit between the two materials. The initial construction cost for Aluminium and Steel are USD 45506 and USD 6808 respectively involving 23.5 metric ton for Aluminium and 67.0 metric tons for steel. In term of investment, offshore support vessels using Aluminium have shorter payback period of 7.9 years and 8.4 years for steel inclusive of the costs of maintenance and operation. This exercise indicates Aluminium alloy is more economical than steel as construction material for deckhouse of offshore support vessel due to its light weight, lower maintenance and increase earning capacity (more cargo).